Rain induced attenuation studies using RazakSAT space-Earth links - Nuroddin, Amirah; Ismail, Ahmad Fadzil; Badron, Khairayu; Zulkurnain, Nurul Fariza; Ismail, Maszlan; Halim, Salim (IEEE, 2013)
Rain induced attenuation is the main reason for the decrease of Space-Earth communication links’ received signal strength. This is more perceptible in the tropical regions due to copious heavy rainfall throughout the years. RazakSAT is a Malaysian remote sensing satellite that utilizes two frequencies which are the X-band and S-band. The X-band frequency is conventionally set aside for military or government organizations. This frequency differs from the common commercial frequencies. The attributes of X-band satellite communication hardware are expected to be designed specifically for military operations. The appropriate margin should be incorporated to ensure reliable and continual communication. Rain induced attenuation data involving S-band and X-band measurements from Malaysia RazakSAT’s satellite have been analyzed. The rain attenuation at higher frequency X-band (8 GHz) was estimated from the values at 3 GHz (S-band) frequency by the use of frequency scaling equation from established models. The paper highlights the assessments of the two RazakSAT’s satellite-Earth transmission link’s fluctuations during precipitations. The main research objective is to derive the appropriate frequency scaling equation of S-band to X-band applicable in tropical environment